Far-Infrared Radiative Properties of Water Vapor and Clouds in Antarctica - Giovanni Bianchini; Massimo Del Guasta; Luca Palchetti; Gianluca Di Natale (Bulletin of the American Meteorological Society, 2015)
Abstract Water vapor and clouds are among the most important greenhouse components whose radiative features cover all the broad spectral range of the thermal emission of the atmosphere. Typically more than 40% of the total thermal emission of Earth occurs in the far-infrared (FIR) spectral region from 100 to 667 cm−1 (wavelengths from 100 to 15 µm). Nevertheless, this spectral region has not ever been fully covered down to 100 cm−1 by space missions, and only a few ground-based experiments exist because of the difficulty of performing measurements from high altitude and very dry locations where the atmosphere is sufficiently transparent to observe the FIR emission features. To cover this lack of observations, the Italian experiment "Radiative Properties of Water Vapor and Clouds in Antarctica" has collected a 2-yr dataset of spectral measurements of the radiance emitted by the atmosphere and by clouds, such as cirrus and polar stratospheric clouds, from 100 to 1,400 cm−1 (100–7 µm of wavelength), including the underexplored FIR region, along with polarization-sensitive lidar observations, daily radiosondes, and other ancillary information to characterize the atmosphere above the site. Measurements have been performed almost continuously with a duty cycle of 6 out of 9 h, from the Italian–French base of Concordia at Dome C over the Antarctic Plateau at 3,230 m MSL, in all-sky conditions since 2012. Because of the uniqueness of the observations, this dataset will be extremely valuable for evaluating the accuracy of atmospheric absorption models (both gas and clouds) in the underexplored FIR and to detect possible daily, seasonal, and annual climate signatures.